Positive effects of molybdenum on the biomineralization process on the surface of low-alloy steel catalyzed by Bacillus subtilis - Guo, Zhangwei; Feng, Qun; Guo, Na; Yin, Yansheng; Liu, Tao (Frontiers in Microbiology, 2024)
The adhesion of microorganisms and the subsequent formation of mineralized layers in biofilms are of great significance in inhibiting the corrosion of metal materials.In this work, we found that the adhesion and subsequent mineralization of Bacillus subtilis on the surface of low-alloy steel are influenced by the molybdenum in the material. The addition of molybdenum will lead to increased adhesion of B. subtilis on the material surface, and the subsequent biomineralization ability has also been improved. Through transcriptome and physiological and biochemical tests, we found that molybdenum can affect the chemotaxis, mobility and carbonic anhydrase secretion related genes of B. subtilis, and then affect the formation and mineralization of the biofilm of B. subtilis.